Determination of the frequency and influence of senile asthenia syndrome on older patients' treatment results in urgent abdominal surgery - Danyliuk, M. B.; Zavhorodniy, S. M.; Shvets, V. M.; Kubrak, M. А.; Данилюк, Михайло Богданович; Завгородній, Сергій Миколайович; Швець, Володимир Миколайович; Кубрак, Михайло Анатолійович (My University, 2024)
Modern demographic data indicate a constant increase in the quantity older people in the general population structure. With age, the body is affected by many factors that lead to senile asthenia syndrome. The study is devoted to the evaluation of the influence of senile asthenia syndrome on older patients' treatment in emergency abdominal surgery for improvement. Materials and methods of the study. Examination and evaluation of the treatment results of 161 (100.0%) patients was based on the Municipal non-commercial enterprise "City Hospital of Emergency and Rapid Medical Care". In the first part of the group, 81 (50.3%) patients were diagnosed with cholelithiasis (CHD) and acute cholecystitis. The second part of the group of 80 (49.7%) patients was diagnosed with perforation of a stomach or duodenal ulcer. All patients were examined and operated urgently. Senile asthenia syndrome was assessed using the Edmonton Freil scale [11]. Markers of senile asthenia were: total protein, albumin, somatotropic hormone and interleukin 6. Results: It was established that hypoproteinemia with a total protein level indicators of 61.35 (55.00; 70.00) g/l, p = 0.0009, U = 1224.0 and dysproteinemia was determined in the main study group. The albumin level in the main group is also significantly reduced - 29.75 (24.70; 35.70) g/l, p = 0.0072, U = 2268.0. The level of somatotropic hormone was considerably lower in the main group 0.89 (0.12, 1.28) mlU/l compared to the comparison group 2.40 (0.33, 3.96) mlU/l, p = 0.0030, U = 2248.5. This indicated the presence of sarcopenia syndrome. The interleukin 6 level in both study groups exceeded the norm. A significant increase in the frequency and mortality of postoperative complications was determined in the group of asthenia patients. Conclusions. The frequency of senile asthenia syndrome was 50.3% among patients in emergency abdominal surgery. The Edmonton Freil scale can be a quick and effective method of diagnosing senile asthenia syndrome in emergency abdominal surgery.
Keywords: senile asthenia; sarcopenia; malnutrition; somatotropic hormone; interleukin 6